2014
DOI: 10.1155/2014/613078
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Encoding Enzymes Involved in the One Carbon Cycle in Rat Placenta is Determined by Maternal Micronutrients (Folic Acid, Vitamin B12) and Omega-3 Fatty Acids

Abstract: We have reported that folic acid, vitamin B12, and omega-3 fatty acids are interlinked in the one carbon cycle and have implications for fetal programming. Our earlier studies demonstrate that an imbalance in maternal micronutrients influence long chain polyunsaturated fatty acid metabolism and global methylation in rat placenta. We hypothesize that these changes are mediated through micronutrient dependent regulation of enzymes in one carbon cycle. Pregnant dams were assigned to six dietary groups with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Our data indicates the beneficial effects of vitamin B 12 and omega-3 fatty acid supplementation across two generations on brain development and function. It is likely that there is an interaction between vitamin B 12 and omega-3 fatty acid possibly through one-carbon cycle and series of our earlier studies have well demonstrated this association in both animals and humans [14][15][16][17][18].…”
Section: Figmentioning
confidence: 83%
See 1 more Smart Citation
“…Our data indicates the beneficial effects of vitamin B 12 and omega-3 fatty acid supplementation across two generations on brain development and function. It is likely that there is an interaction between vitamin B 12 and omega-3 fatty acid possibly through one-carbon cycle and series of our earlier studies have well demonstrated this association in both animals and humans [14][15][16][17][18].…”
Section: Figmentioning
confidence: 83%
“…Abbreviations: BDNF, brain derived neurotrophic factor; CREB, cAMP response element-binding protein; DHA, docosahexaenoic acid; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; RME, reference memory error; RWME, reference working memory error; Trk, tropomyosin receptor kinase; WME, working memory error. fatty acids like docosahexaenoic acid (DHA) in the one carbon cycle [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have reported gene specific expression changes in the rat placenta in response to increased levels of folate in the maternal diet [42,43], to the best of our knowledge this is the first report describing gene expression changes in response to low maternal folate (or methyl donor) intake in this organ, and the first study to investigate this at the transcriptomic level. However, previous studies have used transcriptomic approaches to investigate gene expression changes in the liver in response to low folate-containing diets [33,34,35,36,44,45] so we compared our data with outcomes from these studies.…”
Section: Discussionmentioning
confidence: 93%
“…The same 10Â FA supplementation in rats before and during gestation led to offspring with a 42% decrease in seizure threshold while in vitro, acute FA treatment in neurons induced hyper-excitability and cell bursting (Girotto et al, 2013). Rats fed a maternal high FA and low B12 diet had pups with lower mRNA levels of two key enzymes in the methyl donor metabolic pathway, MTHFR and methionine synthase (Khot et al, 2014). Mother rats with an imbalance in B12 have pups with reduced antioxidant enzymes at birth, while brain oxidative stress was higher in pups of mothers given a high FA and low B12 diet (Roy et al, 2014).…”
Section: Animal Studies On Effects Of Altering Methyl Donor Intakementioning
confidence: 96%